Wavelength division multiplexing through LED spectral slicing - 444617 Shee, Yu Gang (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Electrical Engineering (Telecommunication)) - Universiti Teknologi Malaysia, 2003